N-ACETYLCYSTEINE SEBAGAI TERAPI TOKSISITAS ACETAMINOPHEN - Reghina Pratiwi Hidayat (Yayasan Pendidikan Medika Indonesia, 2020)
Acetaminophen is an effective oral analgesic, with few side effects when used at the recommended dosage. However, acetaminophen poisoning is common and potentially fatal. Acetaminophen is the most widely used analgesic but also the leading cause of acute liver failure. Liver toxicity can occur even at therapeutic doses especially in alcoholic patients, in subjects with chronic liver disease, NAFLD, cardiopulmonary disease, malnutrition, or when acetaminophen is used concurrently with other drugs that stimulate the CYP pathway. Acetaminophen (APAP) is a drug that is widely used in the community with few side effects. Therefore, some patients affected by APAP hepatotoxicity have an excessive intake of APAP doses. This breakdown is mainly produced by one of the APAP metabolites: N-acetyl-para-benzo-quinone imine (NAPQI), which is highly toxic. The dose of drug taken and the length of time taken from APAP to N-acetylcysteine ​​(NAC) therapy are the most important determinants of the development and severity of APAP hepatotoxicity. NAC is an antidote to APAP poisoning, and can be given orally or intravenously. Finally, a multidisciplinary approach with support from the Psychiatry, Intensive Care Unit and the Department of Gastroenterology and Digestion will be needed, especially in the case of autolysis trials and severe liver failure.